The Impact of Human T-Lymphotrophic Virus Type I/II Infection on the Prognosis of Sexually Acquired Cases of Acquired Immunodeficiency Syndrome - Gotuzzo Herencia, José Eduardo (1992)
Twenty (18%) of 111 Peruvian men with sexually acquired human immunodeficiency virus infection were found also to be infected with human T-lymphotrophic virus type I or II in a retrospective study. At the time of data evaluation, 75 patients had reached Centers for Disease Control stage IV (clinical acquired immunodeficiency syndrome) and had not received antiviral medication; mortality in this group was 63.3% (38/60) among patients infected with human immunodeficiency virus alone and 80% (12/15) in the dually infected group. Of the 50 patients who had died, survival time from onset of stage IV to death was shorter in the dually infected group (5.02±3.27 months) than in those with human immunodeficiency virus infection alone (10.07±4.42 months). In Peru, sexually acquired human immunodeficiency virus infection in men is often accompanied by human T-lymphotrophic virus type I/II infection, and dual retrovirus infection is associated with a shorter survival after onset of clinical acquired immunodeficiency syndrome.